Optimization of P25/CaTiO3nanorod Composite Photocatalysts for High Organic Matter Degradation Performance - Tamarua, Tomoki; Nakamoto, Trang; Taguchi, Kozo (Resourceedings, 2023)
Wastewater is discharged into rivers and oceans without any treatment, causing significant damage to animal health and destroying ecosystems. Semiconductor photocatalysts are attracting attention as an effective means for solving this problem. Among them, titanium-based perovskite semiconductors are expected to be the next-generation photocatalysts because of their wide range of properties, including chemical and optical stability. CaTiO3, in particular, has attracted attention because of its excellent corrosion resistance, low cost, and ease of material synthesis. In this study, CaTiO3 nanorods (CaTiO3NR) were prepared by hydrothermal synthesis. The photocatalytic activity was improved by forming a heterostructure between TiO2 particles (P25) and CaTiO3NR and by optimizing the mass ratio of P25 to CaTiO3NR. Methylene blue solution was used as a pollutant model to evaluate the degradation performance of photocatalysts under UV irradiation. The results showed that controlling the mass ratio of P25 /CaTiO3NR can significantly improve the photocatalytic performance and has better degradation than P25/CaTiO3nanocuboids composite photocatalysts. The highest photocatalytic performance was achieved by the P25 /CaTiO3NR=3:1 composite photocatalyst, which had about 60% more decomposition performance compared to P25.